A winding machine for polarized wire grid of microwave radiometer calibration. (April 2019) - Hu, Yong; Shen, Xin; Hu, Ye; Wang, Maosen; Zhang, Qichao; Zou, Qing; Li, Bin
Polarized wire grid has been used as a low-energy polarization separator in many calibration systems. A novel machine was developed for winding the polarized wire grids with different sizes and shapes. In this paper, the process of design including parameters calculation, structural analysis, and the calibration for the winding device is presented. Finally, taking an oval grid as an example, the fabrication and the testing results is shown. A 250 mm×350 mm oval polarized wire grid is fabricated by using this machine, with 0.1 mm diameter molybdenum wires at the distance of 0.3 ± 0.02 mm. And it achieved the 01. mm flatness requirement. The machine used is robust and can be easily extended to even 200 × 200 mm 2 – 500 mm × 500 mm grids with 0.08–0.2 mm diameter wires at the distance of 0.1–0.5 mm.